Andrés Laguna: Translation and the Early Modern Idea of Europe. - Fernández, José María Pérez (Translation & Literature, 2012)
The life and work of Andrés Laguna (1499-1559) illustrate the role played by scholars, diplomats, and translators in the construction of a multilingual idea of Europe stitched together through the textual networks facilitated by printers and publishers. Laguna also exemplifies the intersection of science and literature with translation and the book market. His intellectual production, in particular his philological abilities placed at the service of scientific and literary translation, are linked to moves towards the establishment of a via media in the theological and political worlds, and with the advocacy of a middle style that frequently resorted to common narrative techniques for the distribution of scientific knowledge.